Slow manifolds for dissipative dynamical systems - Ramm, Alexander G. (My University, 2010)
A class of infinite-dimensional dissipative dynamical systems is defined for which the slow invariant manifolds can be calculated. Large-time behavior of the evolution of such systems is studied.
Keywords: Dissipative systems; Dynamical systems; Attractors; Invariant manifolds; Nonlinear evolution